COMPARATIVE ANALYSIS OF DIFFERENT NEOADJUVANT CHEMOTHERAPY REGIMENS FOR TRIPLE-NEGATIVE BREAST CANCER - P. V. Krivorotko; E. K. Zhiltsova; L. P. Gigolaeva; Sh. M. Khadzhimatova; G. A. Dashyan; K. Yu. Zernov; E. S. Trufanova; А. S. Artemyeva; A. G. Kudaibergenova; V. F. Semiglazov (Опухоли женской репродуктивной системы)
Background. Breast cancer is a heterogeneous disease with a variety of phenotypic forms. Triple-negative breast cancer (TNBC) is one of the most aggressive subtypes characterized by high sensitivity to chemotherapy and early recurrence. Due to the lack of efficiency of standard therapeutic approaches, it appears extremely important to search for new regimens of neoadjuvant polychemotherapy (NAPCT). Objective: to assess the efficiency of different NAPCT regimens for treatment of stages T1N1–3 and T2–4N0–3 locally advanced TNBC and to compare the efficiency of eribulin and paclitaxel in NAPCT of TNBC.Materials and methods. A randomized prospective study to evaluate the efficacy of TNBC treatment is being conducted in the N.N. Petrov National Medical Research Center of Oncology since October, 2015. The study included 61 patients with a median age of 45 years (range 31–76 years). Study participants were treated with 2 different NAPCT regimens: patients in the 1st group received eribulin at a dose of 1.1 mg/m2 on the days 1 and 8 of a 21-day cycle in combination with carboplatin AUC6, patients in the 2nd group received paclitaxel at a dose of 80 mg/m2 on the days 1 and 8 of a 21-day cycle in combination with carboplatin AUC6. Then all patients underwent surgery in different volume (radical mastectomy, organ-preserving surgery, reconstructive plastic surgery) with subsequent FAC adjuvant chemotherapy.Results. So far, 61 patients have been randomized (further calculations are based on the number of operated patients: 24 in the 1st group and 27 in the 2nd group). During the preoperative stage, complete clinical regression was achieved in 11 patients from the 1st group and 15 patients from the 2nd group; partial clinical regression was observed in 13 and 12 patients in groups 1 and 2 respectively. We found that the therapeutic regimen with paclitaxel + carboplatin induced a higher rate of pathologic complete responses (ypCR). After NAPCT, 51 out of 61 patients (84 %) underwent surgical treatment. Pathomorphological examination showed that the frequency of pathologic complete response was 33 % (8 cases) in the 1st group compared to 60 % (16 cases) in the 2nd group. Five patients treated with eribulin + carboplatin developed distant metastases in bones, lungs, brain, postoperative scar and lymph nodes in the neck on average 4 months after surgery.Conclusions. Higher rate of ypCR was observed in patients received paclitaxel + carboplatin.